I have this problem. In my book it doesnt have any examples of this type of problem. Please help!
Code:Radical Equations _________ _______ \/ x^2 + 2x = \/ 10 - x
This is a discussion on Algebra 1 within the A Brief History of Cprogramming.com forums, part of the Community Boards category; I have this problem. In my book it doesnt have any examples of this type of problem. Please help! Code: ...
I have this problem. In my book it doesnt have any examples of this type of problem. Please help!
Code:Radical Equations _________ _______ \/ x^2 + 2x = \/ 10 - x
What is C++?
Square both sides of the equations and then you've got a quadratic equation.
x^2 + 2x = 10 - x
x^2 + 3x - 10 = 0
(x+5)(x-2) = 0
x = -5 or 2
Last edited by JasonLikesJava; 06-04-2002 at 11:21 AM.
OS: Linux Mandrake 9.0
Compiler: gcc-3.2
Languages: C, C++, Java
If you go flying back through time and you see somebody else flying forward into the future, it's probably best to avoid eye contact.
-_-;
Uh... can you explain?
How did 2x turn into 3x?
(x+5)(x-2) = 0 ? where did that come from?
What is C++?
He "moved" it from the right side to the left side. Look at this equation:How did 2x turn into 3x?
3 = 2 + 1
That is the same as:
3 - 1 = 2
You can add, subtract, multiply and divide with whatever you want only if you do the same on both sides. What Jason did was add x on both sides.
2x + x turned into 3x
and -x + x turned into 0 (nothing)
MagosX.com
Give a man a fish and you feed him for a day.
Teach a man to fish and you feed him for a lifetime.
so -2 and 5 are factors of 10. Which is number c.
the sum of the factors of c have to equal b wich is 3.
-2 + 5 = 3..
Did I get it?
What is C++?
okay... now lets say I have a problem like this?
that has a radical expresion on just one side... can I work it like this?Code:______ \/ x + 6 = x + 4
x + 6 = x^2 + 16
What is C++?
x^2 + 3x - 10 = 0(x+5)(x-2) = 0 ? where did that come from?
Original equation
x^2 + (2 * (3 / 2)) x - 10 = 0
2 * (3 / 2) is the same as 3. Multiply by 2 and then divide with 2 and you get the same number as before
x^2 + (2 * (3 / 2)) x + (3 / 2)^2 - (3 / 2)^2 - 10 = 0
First you add (3 / 2)^2, then you subtract it, so you haven't changed the value of the equation
(x + (3 / 2))^2 - (3 / 2)^2 - 10 = 0
Using the rule (a + b)^2 = a^2 + 2 * a * b + b^2 (sorry, don't know the english name of it ) you can change the first three terms of step 3 into the blue coloured part in this step
(x + (3 / 2))^2 - (9 / 4) - (40 / 4) = 0
3^2 equals 9 and 2^2 equals 4. I also change 10 into (40 / 4), which is the same thing
(x + (3 / 2))^2 - (49 / 4) = 0
-9 - 40 equals -49
(x +(3 / 2))^2 = (49 / 4)
Add (49 / 4) to both sides (see my previous post)
x + (3 / 2) = +/- sqrt( 49 / 4 )
Take the square root of both sides. Notice the +/-, since both a and -a is a^2 when squared (is this a real word?).
x = -(3 / 2) +/- (7 / 2)
Subtract (3 / 2) from both sides
x1 = -(10 / 2) = -5
x2 = (4 / 2) = 2
Since we have a +/-, x have two values (unless it's a double root). -3 - 7 is -10, and -3 + 7 is 4
If you put in any of these values in (x + 5)(x - 2) = 0, you see that the left side has the value 0, and the equation is correct.
Hope this helps a little. Algebra can be tough sometimes .
Last edited by Magos; 06-04-2002 at 12:06 PM.
MagosX.com
Give a man a fish and you feed him for a day.
Teach a man to fish and you feed him for a lifetime.
............................................
(Vicious is suffering from a braon freeae that Magos has caused him)
What is C++?
No, the correct would be:Originally posted by Vicious
can I work it like this?
x + 6 = x^2 + 16
x + 6 = (x + 4)^2
x + 6 = x^2 + 2 * 4 * x + 4^2
MagosX.com
Give a man a fish and you feed him for a day.
Teach a man to fish and you feed him for a lifetime.
I wasn't sure how much explaining to do since I wasn't sure at what level you were in in Algebra I.
--edited--
Last edited by JasonLikesJava; 06-04-2002 at 12:15 PM.
OS: Linux Mandrake 9.0
Compiler: gcc-3.2
Languages: C, C++, Java
If you go flying back through time and you see somebody else flying forward into the future, it's probably best to avoid eye contact.
Once you get x^2 + 3x - 10 = 0 you can use the equation
Where a is what is in front of x^2 (1), b is what is in front of x (3) and c is -10Code:_________ x = -b (+/-) \/ b^2 - 4ac -------------------------- 2a
OS: Linux Mandrake 9.0
Compiler: gcc-3.2
Languages: C, C++, Java
If you go flying back through time and you see somebody else flying forward into the future, it's probably best to avoid eye contact.
Thanks for your help..
I guess I might can get through with Algebra before next school year starts
What is C++?
if you like this wait until calculus.
f(x) = x^3+2x^2+5x+3
synthetic division, first and second derivatives, and all that fun stuff